2010
DOI: 10.1140/epjc/s10052-010-1468-2
|View full text |Cite
|
Sign up to set email alerts
|

Absolutely anticommuting (anti-)BRST symmetry transformations for topologically massive Abelian gauge theory

Abstract: We demonstrate the existence of the nilpotent and absolutely anticommuting Becchi-Rouet-Stora-Tyutin (BRST) and anti-BRST symmetry transformations for the four (3 + 1)-dimensional (4D) topologically massive Abelian U(1) gauge theory that is described by the coupled Lagrangian densities (which incorporate the celebrated (B ∧ F ) term). The absolute anticommutativity of the (anti-) BRST symmetry transformations is ensured by the existence of a Curci-Ferrari type restriction that emerges from the superfield forma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…However, these models suffer from the problems, connected with renormalizability, consistency and unitarity. We have studied these models [5,6,7,8,9,10], within the framework of superfield and Becchi-Rouet-Stora-Tyutin (BRST) formalisms, in the hope that we would be able to propose a model that would be free of the drawbacks of the earlier models [1,2,3,4]. However, it remains still an open problem to construct a 4D consistent, unitary and renormalizable non-Abelian 2-form gauge theory (where the 1-form and 2-form non-Abelian gauge fields are incorporated together).…”
Section: Introductionmentioning
confidence: 99%
“…However, these models suffer from the problems, connected with renormalizability, consistency and unitarity. We have studied these models [5,6,7,8,9,10], within the framework of superfield and Becchi-Rouet-Stora-Tyutin (BRST) formalisms, in the hope that we would be able to propose a model that would be free of the drawbacks of the earlier models [1,2,3,4]. However, it remains still an open problem to construct a 4D consistent, unitary and renormalizable non-Abelian 2-form gauge theory (where the 1-form and 2-form non-Abelian gauge fields are incorporated together).…”
Section: Introductionmentioning
confidence: 99%
“…With the help of superfield formalism, we have derived the off-shell nilpotent as well as absolutely anticommuting (anti-) BRST transformations and also shown that the topological (B ∧ F) term remains unaffected by the presence of the Grassmannian variables when we generalize it on the (4, 2)-dimensional supermanifold [49,50]. In the non-Abelian case, we have found some novel observations.…”
Section: Introductionmentioning
confidence: 80%
“…This implies that the topological term remains invariant modulo a total spacetime derivative term under the operations of BRST and/or anti-BRST transformations. Consequently, the superLagrangian densities (48) and (49) remain invariant (up to a total spacetime derivative) under the action of Grassmannian derivatives due to the nilpotency (i.e. ∂ 2 θ = 0, ∂ 2 θ = 0) and anticommutativity (i.e.…”
Section: (Anti-)brst Invariance Of the Lagrangian Densities Nilpotenmentioning
confidence: 99%
“…The phenomenological aspects of this model have been discussed in [47] which shed light on the various kind of physical processes that are allowed by the standard model of particle physics. We have also studied the 4D (non-)Abelian topologically massive theory within the framework of BRST formalism [48,49]. In earlier work [10], the 4D non-Abelian topologically massive gauge theory has been studied in the context of superfield formalism where the "scalar" and "vector" gauge symmetries have been treated separately.…”
Section: Introductionmentioning
confidence: 99%